Expression of the class A macrophage scavenger receptor on specific subpopulations of murine dendritic cells limits their endotoxin response. - Becker, M; Cotena, A; Gordon, S; Platt, N (2006)
Dendritic cells (DC) function at the interface of innate and acquired immunity and are uniquely sensitive to specific stimuli. Pattern recognition receptors (PRR) on these cells are critically important because of their ability to recognise and initiate responses to conserved microbial-associated molecular signatures. With the exception of Toll-like receptors (TLR), we know relatively little about the specific distribution of other PRR amongst populations of DC. Here, we describe the expression of the murine class A macrophage scavenger receptor (SR-A) and show that it is restricted to specific subpopulations of bone marrow-derived and splenic DC. Importantly, we demonstrate that the receptor significantly alters the response of DC to endotoxin. In contrast to the activities of other PRR that have so far been examined, uniquely SR-A limits the maturation response; SR-A-/- cells display enhanced CD40 expression and TNF-alpha production. We discuss the potential contributions of SR-A to DC biology in the context of the known multiple activities of this receptor.